From Skin to Kidneys: The Cutaneous Clues of Renal Disease in Children - Mario Diplomatico (Mattioli1885, 2020)
Background:  The skin is often seen as a world apart, but not rarely do cutaneous manifestations reveal signs of systemic disease.